Gut microbiota in early life and its influence on health and disease: a position paper by the Malaysian Working Group on Gastrointestinal Health - Lee, Yeong Yeh; Hassan, Siti Asma'; Ismail, Intan Hakimah; Chong, Sze Yee; Raja Ali, Raja Affendi; Amin Nordin, Syafinaz; Lee, Way Seah; Abdul Majid, Noorizan (John Wiley & Sons Australia, 2017)
The role of gut microbiota in early life and its impact on gut health and subsequent diseases remain unclear. There is a lack of research and awareness in this area, especially in the Asia-Pacific region, including Malaysia. This paper reports the position of a Malaysian Working Group on some key issues surrounding gut microbiota in early life and its role in gut health and diseases, as well as experts’ stand on probiotics and prebiotics. The group reached a consensus that certain factors, including elective caesarean; premature deliveries; complementary feeding; use of antibiotics, prebiotics and/or probiotics; and exposure to the external environmental, have an impact on gut microbiota in early life. However, as evidence is lacking, especially from the Asia-Pacific region, further studies are needed to understand how gut microbiota in early life affects subsequent diseases, including allergy, inflammatory bowel disease, obesity and infantile colic. Lastly, although beneficial in acute diarrhoeal disease and probably allergic eczema, probiotics (and/or prebiotics) should be used cautiously in other gut dysbiotic conditions until more data are available.